On the Dynamics and Control of Free-floating Space Manipulator Systems in the Presence of Angular Momentum - Nanos, Kostas; Papadopoulos, Evangelos G. (Frontiers in Robotics and AI, 2017)
In this paper, the control of free-floating space manipulator systems (FFSMS) with non-zero angular momentum (NZAM), for both motions in the joint and Cartesian space, is studied. Considering NZAM, dynamic models in the joint and Cartesian space are derived. It is shown that the NZAM has a similar result to the effect of gravity in terrestrial fixed base manipulators. Based on these similarities, the application of controllers similar to the ones used for the compensation of gravity in terrestrial fixed base manipulators is proposed here, to compensate the effect of angular momentum. To confirm the asymptotic stability of the closed-loop systems, some structural properties of the dynamic models must be satisfied. It is shown that despite the presence of angular momentum, these structural properties still apply. Thus, the proposed controllers can drive the system in the desired position despite the presence of angular momentum. However, the NZAM imposes constraints on the system workspace, where the end-effector can be driven in the Cartesian space. Limitations are discussed and the application of the proposed controllers is illustrated by examples.